2005
DOI: 10.1016/j.engappai.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of user-based and item-based prediction algorithms for recommendation agents

Abstract: Recommendation agents employ prediction algorithms to provide users with items that match their interests. In this paper, several prediction algorithms are described and evaluated, some of which are novel in that they combine user-based and item-based similarity measures derived from either explicit or implicit ratings. Both statistical and decision-support accuracy metrics of the algorithms are compared against different levels of data sparsity and different operational thresholds. The first metric evaluates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…This is a common evaluation practice in systems examined for other domains (e.g. Breese et al 1998;Herlocker et al 2002;Deshpande & Karypis 2004;Papagelis & Plexousakis 2005). Previous evaluation studies have clearly indicated that careful testing and parameterization has to be carried out before a recommender system is finally deployed in a real setting.…”
Section: Assessing Current Statusmentioning
confidence: 99%
“…This is a common evaluation practice in systems examined for other domains (e.g. Breese et al 1998;Herlocker et al 2002;Deshpande & Karypis 2004;Papagelis & Plexousakis 2005). Previous evaluation studies have clearly indicated that careful testing and parameterization has to be carried out before a recommender system is finally deployed in a real setting.…”
Section: Assessing Current Statusmentioning
confidence: 99%
“…The present study of Papagel is and Plexousakis 18 showed that the item-based algorithm performed better than the user-based algorithm. Yu et al 19 found that the Pearson correlation coefficient outperformed the Kendall correlation and that positively correlated neighbors yielded higher accuracy.…”
Section: Techniques Used In Recommendation Systemsmentioning
confidence: 91%
“…The next phase compares the integrated method with other techniques by using the same dataset for both training and testing in each method. The techniques used in the comparison study are collaborative filtering 18 and association rules 20 .…”
Section: Experimental Designmentioning
confidence: 99%
“…• Item-KNN: Neighbourhood based approaches are the most popular and widely used along with MF techniques. Here, model seeks to find the items which are nearest neighbours to the items already purchased by the customers [27].…”
Section: Methods For Comparative Analysismentioning
confidence: 99%